COGNITIVE LEARNING AND ROBOTICS: INNOVATIVE TEACHING FOR INCLUSIVITY - Oralbayeva, Nurziya; Amirova, Aida; CohenMiller, Anna; Sandygulova, Anara (Multimodal Technologies and Interaction, 2022)
We present the interdisciplinary CoWriting Kazakh project in which a social robot acts as a peer in learning the new Kazakh Latin alphabet, to which Kazakhstan is going to shift from the current Kazakh Cyrillic by 2030. We discuss the past literature on cognitive learning and script acquisition in-depth and present a theoretical framing for this study. The results of word and letter analyses from two user studies conducted between 2019 and 2020 are presented. Learning the new alphabet through Kazakh words with two or more syllables and special native letters resulted in significant learning gains. These results suggest that reciprocal Cyrillic-to-Latin script learning results in considerable cognitive benefits due to mental conversion, word choice, and handwriting practices. Overall, this system enables school-age children to practice the new Kazakh Latin script in an engaging learning scenario. The proposed theoretical framework illuminates the understanding of teaching and learning within the multimodal robot-assisted script learning scenario and beyond its scope.
Keywords: Type of access: Open Access; cognitive language learning; robotics; robot-assisted alphabet learning; robot-assisted script learning; alphabet reform; script learning; inclusion